THE EFFECT OF INTEGRITY, ORGANIZATIONAL CULTURE AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE AT PT.BANK MANDIRI (PERSERO) ACEH FUNCTIONAL OFFICE - Asri Bernitzky Saragi; Meilita Tryana Sembiring; Syahyunan (RADJA PUBLIKA, 2023)
The results of dividing the Mean Square regression with the Mean Square residual obtained an F count of92,921with a significance probability value limit of 0.000. While the F table value at a significant level of 5% and df 67 is 2.74. Thus the calculated F value (92,921)greater than F table (2.74) so that a decision can be taken, namely accepting the alternative hypothesis (Ha) and rejecting the hypothesis Ho, that isIntegrity (X1), Organizational Culture (X2), and Employee Engagement (X3) all have an effect on Employee Performance (Y). From the results of the SPSS output, the Adjusted R Square is 0.798. Adjusted valueR Squarethis amount explains, the role of the variables Integrity (X1), Organizational Culture (X2), and Employee Engagement (X3) in influencing Employee Performance (Y) is 0.798 or 79.8%. While the residual (residual value) of the role of these variables is 0.202 or 20.2% influenced by other variables not involved in this study. From the results of the comparison of the regression coefficient values with the standard error, it is obtained that the t value for the influence of the Integrity variable is 6.724 at the limit of a significance probability value of 0.005. While the t-table value at df 69 and a significant level of 5% is 1.994. The results of this calculation indicate that the calculated t value is greater than the t-table value so that a decision can be taken that the alternative hypothesis (Ha) can be accepted and reject the null hypothesis (Ho), meaning that Integrity (X1) partially has a significant effect on Employee Performance (Y ). From the results of the comparison of the regression coefficient values with the standard errorobtainedthe calculated t value for the influence of the Integrity variable is equal to6,210at the limit of significance probability value of 0.000. While the t-table value at df 69 and a significant level of 5% is 1.994. The results of this calculation indicate that the calculated t value is greater than the t-table value so that a decision can be taken that the alternative hypothesis (Ha) can be accepted and reject the null hypothesis (Ho), meaning that Organizational Culture (X2) partially has a significant effect on Employee Performance ( Y). From the results of the comparison of the regression coefficient values with the standard errorobtainedthe calculated t value for the influence of the Employee Engagement variable is equal to6,699at the limit of significance probability value of 0.004. While the t-table value at df 69 and a significant level of 5% is 1.994. The results of this calculation indicate that the calculated t value is greater than the t-table value so that a decision can be taken that the alternative hypothesis (Ha) can be accepted and reject the null hypothesis (Ho), meaning that Employee Engagement (X3) partially has a significant effect on Employee Performance.